Moral development and its relevance to contemporary education: A comparative perspective of Ibn Miskawayh and Lawrence Kohlberg - Muslikhul Ibad; Nunung Dwi Setiyorini (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2025)
Purpose – This study aims to conduct a comparative analysis of moral development theories proposed by Ibn Miskawayh, a classical Islamic ethical philosopher, and Lawrence Kohlberg, a moral development psychologist. It also seeks to identify points of convergence and divergence between their moral concepts that have practical relevance for moral education in the contemporary era. Design/methods/approach – This research employs a qualitative approach, drawing on a literature review and comparative conceptual analysis. Data were collected through an in-depth examination of the primary works of Ibn Miskawayh and Kohlberg, as well as of previous scholarly works discussing their ideas. The analysis compared essential aspects, including educational objectives, curriculum content, educational methods, moral foundations, and moral characteristics. Findings – The study finds a fundamental paradigmatic difference between the two theories. Ibn Miskawayh’s theory is grounded in the Islamic–Aristotelian ethical tradition, with the ultimate goal of moral education being the attainment of true happiness (al-sa‘ādah al-ḥaqīqiyyah). In contrast, Kohlberg’s theory is rooted in cognitive constructivism, focusing on the development of moral reasoning through a series of universal stages culminating in the Universal Ethical Principle of justice. Nevertheless, both thinkers agree that moral development is a hierarchical process that involves the function of reason (‘aql) as the primary determinant in the transition toward mature, internally grounded moral principles. Research implications/limitations – The findings indicate the need for a comprehensive approach to moral education. Ibn Miskawayh’s model is highly relevant for emphasizing character formation and the affective and spiritual dimensions of morality through habituation, which serve as the foundation of moral behavior. Meanwhile, Kohlberg’s model is particularly relevant for developing students’ cognitive abilities and critical moral reasoning. The integration of these two perspectives offers a more holistic framework that balances character formation with the development of moral reasoning capacities. Originality/value – This study contributes to building a theoretical bridge and fostering interdisciplinary dialogue between Islamic ethical philosophy and developmental psychology, offering new insights for addressing the challenges of contemporary moral education.